Human X-chromosome non-coding variation in Latin American populations: A review - Catanesi, Cecilia Ines (2023)
The human X-chromosome non-coding markers, such as short tandem repeats (STRs), single nucleotide polymorphisms (SNPs), insertion-deletions (INDELs) and Alu insertions, are useful for revealing relationships among populations and for the identification of individuals. In the last decades, a number of studies have been performed to determine the genetic structure of Latin American populations by using X-chromosome markers. These studies provided useful information regarding the genetic composition of these populations and their relationship with Native American, Asian and European populations. One of the most interesting findings achieved by X-chromosome studies is the bias in the sex ratio of individuals that gave rise to the current Latin American populations, as it was previously observed through the analysis of uniparental markers, and which is undoubtedly evidenced in the differential inheritance of X-chromosome in comparison to autosomes. Besides, the genetic drift process that affected Native American populations is more pronounced in X-chromosome markers than in autosomes. The present review summarizes our current knowledge concerning X-chromosome non-coding polymorphisms studied in Latin American populations.